Nanomedicine of Plant Origin for the Treatment of Metabolic Disorders - Hu, Fang; Sun, Dong-Sheng; Wang, Kai-Li; Shang, Dan-Ying (Frontiers in Bioengineering and Biotechnology, 2022)
Metabolic disorders are major clinical challenges of health that are progressing globally. A concurrence of metabolic disorders such as obesity, insulin resistance, atherogenic dyslipidemia, and systematic hypertension leads to metabolic syndrome. Over the past years, the metabolic syndrome leads to a five- and two-fold rise in diabetes mellitus type II and cardiovascular diseases. Natural products specifically plant extracts have insulin-sensitizing, anti-inflammatory, and antioxidant properties and are also considered as an alternative option due to few adverse effects. Nanotechnology is one of the promising strategies, which improves the effectiveness of treatment and limits side effects. This review mainly focuses on plant extract-based nanosystems in the management of the metabolic syndrome. Numerous nano-drug delivery systems, i.e., liposomes, hydrogel nanocomposites, nanoemulsions, micelles, solid lipid, and core–shell nanoparticles, have been designed using plant extracts. It has been found that most of the nano-formulations successfully reduced oxidative stress, insulin resistance, chronic inflammation, and lipid profile in in vitro and in vivo studies as plant extracts interfere with the pathways of metabolic syndrome. Thus, these novel plant-based nanosystems could act as a promising candidate for clinical applications.